Kandungan Bahan Pengisi Batu Kapur Super pada Campuran HRS - B. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan Universitas Gajah Mada, 1999)
ABSTRAK Large area and a sustainable development program of Indonesia create a high demand of materials. There are many ocal materials, which have not been well exploited. This condition is happened due to lack of information about local materials. â¢ Hot Rolled Sheet B (HRS-B) mixtures have been found in many implementation of road management program in 'ndonesia, especially in Yogyakarta and it's around. In the south of this area, there are many lime stones. There for an attention should be paid on a matter of lime stones filler to be exploited as a filler in HRS-B mixtures. This research indicates that lime stones filler can be a substitution filler of HRS-B mixtures, and its amount should be :orrected by its specific gravity. For the mixture it needs only 4,37 - 7,08% of substitution filler, and given on optimum asphalt content of 6,8 - 7,5%.